2000
DOI: 10.1007/s001250050028
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and non-esterified fatty acid relations to alimentary lipaemia and plasma concentrations of postprandial triglyceride-rich lipoproteins in healthy middle-aged men

Abstract: A cluster of risk factors for Type II (non-insulin-dependent) diabetes mellitus and cardiovascular disease, called the metabolic syndrome, is a common feature of otherwise healthy people living in industrialised countries. Increased visceral adipose tissue depots, insulin resistance with ensuing hyperinsulinaemia and dyslipoproteinaemia including hypertriglyceridaemia, a low HDL cholesterol concentration and a preponderance of small, dense LDL particles are central components of this syndrome [1]. The links be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
4
31
0
1
Order By: Relevance
“…In the vast majority of studies already conducted in the field of postprandial lipid metabolism, both insulin resistance and related hyperinsulinism took part in the abnormal metabolic syndrome exhibited by the subjects (5,12,14,15). Thus, although key data showing a positive association between insulin resistance/hyperinsulinism and exaggerated postprandial lipemia have been obtained, it has not yet been possible to discriminate between the respective roles of insulin resistance or hyperinsulinism on postprandial lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the vast majority of studies already conducted in the field of postprandial lipid metabolism, both insulin resistance and related hyperinsulinism took part in the abnormal metabolic syndrome exhibited by the subjects (5,12,14,15). Thus, although key data showing a positive association between insulin resistance/hyperinsulinism and exaggerated postprandial lipemia have been obtained, it has not yet been possible to discriminate between the respective roles of insulin resistance or hyperinsulinism on postprandial lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Because these patients display both hyperinsulinism and insulin resistance, it is difficult to evaluate the respective role of hyperinsulinism and insulin resistance in the abnormalities of the postprandial lipemia observed. Several studies have shown that the observed accumulation of exogenous triglyceride-rich lipoproteins (TRLs) after a fat-containing test meal positively correlates with both fasting and postprandial plasma insulin levels in normal or obese subjects (5,12,14,15). Some reports, on the basis of indirect arguments, have suggested that insulin resistance is the main factor in this phenomenon (5,12,14,15), and that the amplitude of postprandial lipemia correlates with the severity of insulin resistance (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of early phase insulin has not been clarified since insulin has pleiotropic effects (both directly and indirectly) on exogenous lipoprotein metabolism and endogenous lipoprotein synthesis. 19,20) One of the well-defined molecules that influence the levels of triglycerides is lipoprotein lipase (LPL), which hydrolyzes the triglyceride component of circulating lipoprotein, and decreases the blood triglyceride levels. Insulin is a major stimulator of the postprandial increase of LPL activity, but other reports have suggested that decreased LPL gene expression is mediated by the increase of insulin in rats with postprandial hyperlipidemia.…”
Section: )mentioning
confidence: 99%
“…Postprandial lipoproteins and their remnants may deposit into arterial walls accelerating the development of atheromatous plaques 1 and the postprandial elevation in circulating triglyceride (TG)-rich lipoproteins contributes to the accumulation of small, dense low-density lipoproteins (LDL) and a decrease in cardio-protective high-density lipoproteins (HDL); a combination known as the atherogenic phenotype. 2 In addition, postprandial hyperinsulinaemia, together with the transient postprandial increase in insulin resistance may also contribute to atherogenic progression [3][4][5] and the development of chronic insulin resistance and type 2 diabetes. 6 As humans spend the majority of the day in the postprandial state, interventions which alter postprandial metabolism may have implications for the prevention and management of metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%